Product Analyst & Digital Marketing Training at SMES "Kwt Kenanga" in Ngestiharjo, Kasihan, Bantul, D.I.Y - murniady muchran; Adi Prasetyo; Sir Kalifatullah Ermaya; Firdiyan Syah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The Women Farmers Group (KWT) plays a role as a platform facilitating community participation, especially among women. This service targets one of the KWTs located in Bantul Regency, DIY. The presence of KWT "KENANGA" includes three divisions, with the food division being the focus of this training. The food division of KWT "KENANGA" has various products but has not fully optimized their marketing and sales. The goal of this service is to provide solutions to the issues found with the partners, focusing on enhancing the added value of products through improved packaging and implementing digital marketing to reach a broader market. The training method was conducted in 4 stages (Planning, Implementation, Evaluation, and Reporting) where activities were carried out face-to-face in a forum that presented materials and training simultaneously. As a result of this training, partners were able to practice methods to enhance the added value of their products through packaging and use digital marketing via smartphone media. The conclusion from this training is that KWT "KENANGA" is crucial in understanding and utilizing technology to reach a broader market. Additionally, involving the younger generation is essential as they provide access to information regarding current consumer behavior trends and developments.